SISTEM REMUNERASI BERBASIS KINERJA DALAM MENINGKATKAN KINERJA PEGAWAI DI KECAMATAN SUKAMAHAYA KOTA DEPOK PROVINSI JAWA BARAT - Siti Zulaika (Jurnal Ilmiah Wahana Bhakti Praja, 2016)
AbstractThe low performance of employees of one of them due to poor compensation. The fi x, the systemis given additional remuneration other than salary income of employees (TPP). This study aimsto determine: the remuneration system in the District Sukmajaya; whether the application ofthe remuneration can improve employee performance; and additional problems encounteredin the implementation of the remuneration. The study design is qualitative descriptive, witha saturated sample because researchers wanted to gain a holistic overview and detailed toanswer these research objectives. The results of the study and discussion of remuneration inthe form of salaries and TPP. The amount of TPP is based on the results of the analysis of themeasured positions of responsible work. TPP is given based on the discipline and the measuredperformance of the task implementation report every week to the direct superior. But in realitythe presence of an employee is unable to detect because the tools used are conventional anddo not report on the implementation tasks carried out according to the rules. Conclusion:Remuneration in the form of salaries and the TPP is not feasible and is not fair; Remunerationcan motivate and improve employee performance, but not optimal due to poor application ofthe rules; and presence are still using conventional tools. Recommendation: that TPP minimumof salary, implementation of rules as the basis for the TPP, and soon realized the purchase ofequipment Presence automatically.Keywords: remuneration, employee performance